Epidemic Retinitis with Macular Edema –Treatment Outcome with and without Steroids. (4th July 2021) - Kawali, Ankush; Srinivasan, Sanjay; Mohan, Ashwin; Bavaharan, Bharathi; Mahendradas, Padmamalini; Shetty, Bhujang
ABSTRACT: Purpose : To study treatment outcomes with and without oral corticosteroids in epidemic retinitis (ER). Method : A retrospective, observational study of 35 eyes of 29 patients diagnosed as ER. Days taken for resolution of macular edema and retinitis lesions were compared in patients treated with oral antibiotics (Group 1) and with corticosteroids–antibiotics combination (Group 2). Result : Eighteen eyes of 14 patients and 17 eyes of 15 patients formed Groups 1 and 2, respectively. At the presentation, mean best-corrected visual acuity (BCVA) was 40 and 44 letters and mean central macular thickness was 648 (±243) and 626 (±256) microns in Groups 1 and 2, respectively. Macular edema resolved in 30.83 and 31.94 days; retinitis lesions resolved in 36.71 and 41.41 days in Groups 1 and 2, respectively. BCVA improved to 74 and 77 letters in Groups 1 and 2, respectively. Conclusion : ER with macular edema can be well managed without corticosteroids.